Preventing Sexual Violence Through Bystander Intervention: Attitudes, Behaviors, Missed Opportunities, and Barriers to Intervention Among Australian University Students - Kania, Rachel (Journal of interpersonal violence, 2021)
The concept of bystander intervention is gaining popularity in universities as a mechanism to prevent sexual violence. Prior research has focused on correlates of bystanders’ intentions to intervene and intervention behaviors in situations where there is a risk of sexual violence. The current study builds on this literature by exploring the nature of missed opportunities, including perceived barriers to intervention. In all, 380 Australian undergraduate university students completed an online survey. Measures included a rape myth acceptance scale, bystander intentions to intervene, actual intervention behaviors, missed opportunities for intervention, and perceived barriers for missed opportunities. Promisingly, students reported high levels of intentions to intervene in situations where there was a risk of sexual violence and reported relatively few missed opportunities to do so when these situations did occur. Intervention behaviors varied by important demographic characteristics such as gender, age, attitudes toward sexual violence, and the nature of the situation. Younger female students, with lower levels of rape myth acceptance, who had previously engaged in bystander intervention behaviors were more likely to report intentions to intervene in future risky situations, and female international students reported fewer missed opportunities for intervention. The most common barrier to intervention for identified missed opportunities was a failure to recognize situations as having a potential risk for sexual violence, and students were most likely to intervene in situations when the opportunity to help a friend in distress arose. This study provides some preliminary empirical evidence about bystander intervention against sexual violence among Australian university students, and identifies unique contexts for intervention and what current barriers to intervention may be.